Inspection: a process of vital importance in the territorial entities (2019)
It is important that the territorial entities have clarity of the sources of income with which they have within their jurisdiction, such as: Property Tax, Industry and Commerce Tax, Urban Delineation, Notices and Boards, Public lighting, among others; in this way a work plan can be made where collection strategies are established to guarantee the satisfaction of basic needs and subsequent